Predictors of travel motivations: The case of domestic tourists to island destinations in northwest of Malaysia - Kasim, Azilah; Dzakiria, Hisham; Park, Chansoo; Mohd Noor, Nor Azila; Mokhtar, Muhammad Fauzi; Rashid Radha, Jasmine Zea Raziah Radha (Routledge, 2013)
This paper examines the role of key socio demographic attributes and trip characteristics in travel motivations of domestic tourists to island destinations.A total of 1780 useful survey responses were collected over a period of 6 months via an assisted survey.Analysis using independent sample t-test and one-way ANOVA revealed that only the “travel companionship status” in respondents' trip characteristics significantly influences the travel motivations of domestic tourists. Particularly, family and friends were found to be a major influence on the travel motivations of domestic tourists.The study concludes that the travel motivations of domestic tourists are more influenced by who individuals choose to travel with, therefore reflecting the issue of local conditions. The findings support Gilbert's (1991, Progress in tourism, recreation and hospitality management. London: Belhaven) theory of family influence in travel decisions. However, it adds that where the population is relatively young, friends can also be a major influence.Theoretical and managerial implications are then discussed.